Preparation method of ceramic copper-clad plate and obtained ceramic copper-clad plate

Through high-speed arc spraying and laser cleaning technology, the problems of high cost and unstable bonding force in the ceramic copper clad process are solved, and efficient and reliable combination between the ceramic substrate and the copper layer is achieved, which is suitable for the production of high-thickness electronic devices.

CN119653620APending Publication Date: 2025-03-18浙江巴顿焊接技术研究院
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411825496.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing ceramic copper clad process has problems such as high cost, low production efficiency, unstable bonding force and low applicability, especially in obtaining high-quality ceramic copper clad plates.

Method used

High-speed arc spraying technology is used to spray aluminum alloy transition coating and non-alloy copper coating on ceramic substrates. The ceramic surface is roughened by laser cleaning technology to form the substrate surface to improve binding force.

Benefits of technology

It realizes a dense and reliable combination between the ceramic substrate and the copper layer, reduces production costs, improves the simplicity and applicability of the process, and is suitable for electronic devices with greater thickness requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653620A_ABST
    Figure CN119653620A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic-metal composite materials, in particular to a preparation method of a ceramic copper-clad plate and the obtained ceramic copper-clad plate. The transition coating and the copper conductive coating are prepared through the high-speed electric arc spraying technology, compact and reliable combination between the ceramic substrate and the conductive copper layer is achieved, the copper conductive coating with the larger thickness can be conveniently prepared on the ceramic substrates of different sizes, and the method can be applied to an ultra-high-power IGBT module with the larger thickness requirement. And the fields of high-speed rails, high-power LEDs, electric automobiles, 5G communication modules and the like are provided. According to the method, the ceramic surface is coarsened preferably through a laser cleaning technology, so that the smooth surface of the ceramic substrate can form a coarsened surface with uniform concave-convex depth, oil stains and the like on the surface can be cleaned, the bonding area of the ceramic substrate and the transition coating can be increased, and mutual embedded strong interface bonding between the ceramic substrate and the transition coating is also facilitated; and the binding force between the two is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic-metal composite materials, and in particular to a preparation method of a ceramic copper-clad laminate and the obtained ceramic copper-clad laminate. Background Art

[0002] Commonly used technologies for ceramic copper coating include thin film method, thick film method, direct copper coating (DBC, Direct Bonded Copper), laser activated metallization (LAM, Laser Activation Metallization), active metal vacuum brazing (AMB, Active Metal Bonding) and many other processes.

[0003] The thin film method is to pre-treat the ceramic substrate and then deposit a 200-500nm Cu layer by magnetron sputtering, then complete the pattern transfer through film lamination, exposure, development and other processes, and then electroplate the Cu layer to the required thickness. The production equipment of the thin film technology in this process is expensive, requires high vacuum conditions, has low production efficiency, and the bonding force between the metal layer and the substrate is unstable. Before depositing the Cu layer, a layer of Ti must be deposited as a transition, which increases the complexity of the process.

[0004] The thick film method is a method of directly depositing conductive paste on a pre-treated substrate and forming conductive circuits and electrodes through high-temperature sintering. This process is simple, but has obvious disadvantages. It is limited by the size of the conductive paste and the screen. The used paste has high viscosity and is prone to clogging. The electrical performance of the conductive circuit is poor, and it is only suitable for electronic devices with low power and size requirements.

[0005] The DBC method directly bonds the copper foil to the Al2O3 ceramic substrate surface under N2 protection at 1065-1083°C. The ceramic copper-clad laminate obtained by this process has low reliability, and pores are easily generated between the copper foil and the ceramic, resulting in unstable performance of the final device. It is only used for Al2O3 ceramics and has low applicability.

[0006] The laser activated metallization process combines the laser direct writing process with the traditional chemical plating process to further improve the forming efficiency. It is suitable for the direct preparation of conductive lines on the surface of various ceramic materials, and is not limited by the size, shape and composition characteristics of the sample. The disadvantage of this process is that the chemical plating process generally uses expensive and environmentally polluting palladium salts as activators and has a slow deposition rate.

[0007] The ceramic copper-clad substrate obtained by AMB technology utilizes the reaction between active elements and ceramics to achieve the connection between copper and ceramics, and has high reliability. However, traditional active solders such as Ag-Cu-Cu-Ti alloy solders are used, which are expensive, and the cost of the obtained ceramic copper-clad substrate is relatively high.

[0008] China CN202410059561.2 provides a ceramic copper-clad laminate material and a preparation method thereof, wherein the ceramic copper-clad laminate material is prepared by spraying a metal transition coating and a copper alloy layer on a ceramic substrate, wherein the ceramic substrate comprises aluminum nitride ceramic or silicon nitride ceramic; the metal transition coating comprises two elements of nickel and titanium, wherein nickel and titanium each account for 50% atomic ratio in the metal transition coating; and the copper alloy layer comprises a copper alloy, wherein the copper alloy comprises the following components based on the weight of the copper alloy: Ni 2.0-4.0%, Si 0.3-1.0%, Mg 0.05-0.5%, Al 0.1-1.2%, Cr 0.05-0.5%, Ti 0.05-0.7%, Zr 0.05-0.5%, and the remainder of Cu. This scheme has the following aspects to be improved: (1) The metal raw material needs to be prepared into powder, and the morphology and particle size of the powder will affect the coating performance, and the preparation is complex and costly. (2) The preparation of the metal transition coating and the copper layer requires the use of alloys containing expensive metals such as Ti and Zr, which is costly. (3) The copper layer requires the use of a specific alloy, which is difficult to obtain.

[0009] Therefore, in order to meet the needs of actual applications, it is urgent to develop a ceramic surface copper coating solution with low cost, easy access to raw materials, high degree of bonding and simple process. Summary of the invention

[0010] In view of the existing phenomenon, the present invention provides a method for preparing a ceramic copper clad laminate and the obtained ceramic copper clad laminate, which at least solves one of the above technical problems.

[0011] The technical solution provided by the present application is: a method for preparing a ceramic copper clad laminate, comprising the following steps:

[0012] S1, roughening the ceramic surface to form a substrate surface;

[0013] S2, spraying a transition coating on the outside of the substrate surface using a high-speed arc spraying device, wherein the transition coating includes an aluminum alloy;

[0014] S3. Use high-speed arc spraying equipment to spray a copper coating on the outside of the transition coating, where the copper coating includes non-alloy copper.

[0015] Further, the ceramic includes one of Si3N4, Al2O3 or AlN.

[0016] Furthermore, the transition coating is composed of AlMg5. The transition coating can form a firm bond with both the ceramic substrate and the copper coating.

[0017] Furthermore, in step S2, high-speed arc spraying is performed using ER5356 welding wire.

[0018] Furthermore, the thickness of the transition coating is 80-100 μm. At this thickness, the transition coating can form a firm bond with both the ceramic substrate and the copper layer without wasting materials.

[0019] Furthermore, the copper coating thickness is 100-3000 μm. The copper coating thickness within this range can be well combined with the transition coating. The specific thickness can be selected according to the use requirements.

[0020] Furthermore, the roughening process in step S1 is a laser ablation roughening process.

[0021] Furthermore, in step S3, high-speed arc spraying is performed using ERCu welding wire.

[0022] Furthermore, the compressed gas source pressure used by the high-speed arc spraying equipment is not less than 0.6 MPa.

[0023] Another technical solution provided by the present application is: a ceramic copper-clad laminate prepared by the above-mentioned ceramic copper-clad laminate preparation method.

[0024] The beneficial effects of this application are:

[0025] 1. The present invention prepares the transition coating and the copper coating through high-speed arc spraying technology, thereby achieving a dense and reliable combination between the ceramic substrate and the conductive copper layer. It can be convenient to prepare a thicker copper conductive coating on ceramic substrates of different sizes, and can be applied to ultra-high-power IGBT modules with greater thickness requirements, such as high-speed rail, high-power LEDs, electric vehicles, 5G communication modules and other fields.

[0026] 2. The laser cleaning technology and high-speed arc spraying technology of the present invention can adopt semi-automatic laser or combine with robot automated laser processing. The automated and stable process is conducive to improving work quality and has broad application prospects.

[0027] 3. The present invention roughens the ceramic surface through laser cleaning technology, so that the smooth surface of the ceramic substrate can form a roughened surface with uniform depth of concave and convex, and at the same time, the oil stains on the surface can be cleaned, which can not only increase the bonding area between the ceramic substrate and the transition coating, but also help to form a strong interface bonding between the two that is "embedded" with each other, thereby improving the bonding force between the two.

[0028] 4. The present invention preferably uses laser cleaning technology, which is simple, convenient, high-speed and environmentally friendly. Laser cleaning technology has obvious advantages in efficiency, accuracy, position, etc., without environmental pollution caused by chemical corrosion technology, can effectively avoid surface damage caused by sandblasting, and does not require other auxiliary processes and tools. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings, which are incorporated into and constitute a part of the specification, illustrate embodiments of the present invention and are used together with the description to explain the principles of the present invention. The drawings described below are some embodiments of the present invention, but not all embodiments. For those of ordinary skill in the art, other drawings can be obtained from these drawings without creative work.

[0030] Figure 1 A schematic diagram of the structure of a ceramic copper-clad laminate prepared by the preparation method of the ceramic copper-clad laminate of the present application;

[0031] Reference numerals:

[0032] Ceramic substrate 1, transition coating 2, copper coating 3. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the description of this application, unless otherwise clearly specified and limited, the terms "connected", "connected", and "fixed" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0035] The present disclosure provides a specific embodiment of a method for preparing a ceramic copper clad laminate, comprising the following steps:

[0036] Step S1, using a laser cleaning device to perform ablation and roughening treatment on the ceramic substrate 1 on one side of the copper cladding layer to prepare a substrate surface with a concave and convex surface as a bonding interface with the transition coating 2.

[0037] The difference in expansion coefficient between the ceramic copper clad laminate substrate and the Si-based chip determines whether the connection layer will deform and fall off when the temperature changes greatly. The ceramic copper clad laminate substrate needs to focus on the matching of the thermal expansion coefficient with the Si-based chip and its thermal conductivity. The most widely used Al2O3 ceramic substrate has a low thermal conductivity and a large difference in expansion coefficient with the chip, and its limitations are obvious. The Si3N4 ceramic substrate is closer to the thermal expansion coefficient of the Si-based chip, has a higher thermal conductivity, and has a wider application. This embodiment uses a commercially available 2mm thick Si3N4 ceramic substrate.

[0038] The smooth surface of the Si3N4 ceramic substrate is roughened by an efficient laser cleaning equipment, which can clean the oil stains on the surface while ablation and roughening the surface. The roughening of the surface directly affects the bonding of the coating, which is determined by processing parameters such as laser spot shape, laser power, and laser scanning width. This embodiment uses a pulsed laser with a power of 50W, the working atmosphere is compressed air, the laser output wavelength is 1064-1080nm, and the laser scanning width can be set in the range of 10 to 100mm. The laser pulse frequency, scanning speed and scanning width are matched to be suitable for ceramic substrates of irregular sizes. Rotate the sample angle and repeat the laser ablation step until the surface of the silicon nitride ceramic substrate is smooth and the surface is completely roughened.

[0039] In order to obtain a pre-processed surface suitable for spraying, a series of tests were carried out with reference to the laser processing parameters in Table 1.

[0040] Table 1 Laser processing parameters and roughening effects of 2mm thick Si3N4 ceramic substrate

[0041]

[0042] The results show that if the height from the lens is too low or the scanning width is too large, the power is too large, and the energy accumulates too much on the ceramic substrate, the ceramic substrate is prone to overheating and cracking. For a 2mm thick Si3N4 ceramic substrate, the laser spot shape is a double helix; the laser power is 20-40W; the laser pulse frequency is 20KHz; the laser scanning width is 50-60mm, and the laser scanning speed is 5000mm / s, the surface roughening effect is better.

[0043] Compared with the commonly used sandblasting roughening or corrosion roughening, the laser roughening provided in this embodiment can, on the one hand, make the bonding strength of the sprayed coating higher, and facilitate the preparation of thicker coatings; on the other hand, it has fewer steps and higher efficiency.

[0044] Step S2: spraying a transition coating on the laser activated substrate surface obtained in step S1. AlMg5 (ER5356) welding wire is prepared by high-speed arc spraying process. The diameter of the welding wire can be or And other common specifications.

[0045] The high-speed arc spraying system includes a dedicated power supply for arc spraying, a control device, an arc spray gun, a wire feeding mechanism and a compressed air supply system. During operation, two welding wires are continuously fed into the combustion chamber of the arc spray gun by the wire feeding mechanism, leaving a 1-2mm gap between the two ends of the welding wires in the arc spray gun. After turning on the power switch, the arc generated between the two welding wires is used to melt the welding wires, and compressed air with a pressure of 0.6-0.7MPa is introduced into the combustion chamber to cool the combustion chamber, and a high-speed airflow is formed in the special nozzle chamber to atomize the molten metal, and the atomized metal particles are accelerated to spray onto the roughened surface of the ceramic substrate to form a transition coating. When welding wire, the current is 115-125A, the voltage is 40V, and the spraying distance is 100-150mm. The coating thickness is less than 80 μ When the thickness of the bonding layer is less than 100 μm, the thickness of the bonding layer is uneven and the thick copper coating prepared subsequently is easy to fall off. μ m affects the total thickness of the coating and the performance of the copper cladding. The coating thickness is preferably 80-100 μ m, the transition coating can form a strong bond with both the ceramic substrate and the copper layer.

[0046] Step S3: Spraying a copper coating 3 on the transition coating obtained in step S2. The same high-speed arc spraying equipment and pure copper (ERCu) welding wire as in step S2 are used. The diameter of the welding wire can be or .use When welding the wire, the current is 180-200A, the voltage is 34V, and the spraying distance is 160-180mm. In other embodiments, the thickness of the copper coating can be set according to different design requirements.

[0047] The preparation method of the comparative sample is basically the same as that of the above specific embodiment, except that the pressure of the compressed gas source used in steps S2 and S3 is 0.3 MPa.

[0048] Test Example 1

[0049] In order to test the conductive properties of the ceramic copper-clad laminate obtained according to the embodiment of the preparation method of the ceramic copper-clad laminate, a four-probe test HG2511 DC low resistance tester was used to test the resistivity of Cu coatings of different thicknesses under the same conditions. The measured value reading was the square resistance value, and the average value of ten square resistance values ​​was taken to calculate the resistivity. The test results are shown in Table 2.

[0050] Table 2 Cu coating resistance test results

[0051] Sample No. thickness Average square resistance R Resistivity ρ 8 250μm Cu coating 305.6mΩ 152.8uΩ·m 9 350μm Cu coating 339.0mΩ 169.5uΩ·m 10 500μm Cu coating 378.0mΩ 113.4uΩ·m 11 1mm copper plate 107.6mΩ 57.4uΩ·m Comparison sample 1 500μm Cu coating 661.0mmΩ 198.3uΩ·m

[0052] in

[0053] ρ-resistivity; W-film thickness; d-sample width; l-sample length

[0054] The test results show that the resistivity of the Cu coating sprayed by high-speed arc spraying is relatively large, but not more than 3 times the resistivity of 1mm pure copper plate, which is due to the oxidation of the sprayed particles in the air. The conductivity of the Cu coating of the comparison sample is much lower than that of the Cu coating sprayed by high-speed arc spraying due to insufficient atomization of the metal particles, high porosity and rough surface.

[0055] Test Example 2

[0056] In order to test the bonding strength of the ceramic copper clad laminate developed in the present invention, a coating bonding strength test specimen was prepared according to the preparation method of the ceramic copper clad laminate, and a tensile test was carried out in a universal testing tensile machine according to GB / T 8642 standard. The results are shown in Table 3.

[0057] Table 3 Cu coating bonding strength test results

[0058]

[0059] The test results show that the bonding strength between Cu coating and AlMg5 coating, and the bonding strength between AlMg5 coating and ceramic are higher than the bonding strength of AlMg5 coating itself. μ m, the maximum strength of AlMg5 coating can reach 9.42MPa. As for the comparison sample, due to the insufficient degree of metal ion atomization, the AlMg5 coating and Cu coating did not form an effective bond, and the strength was lower.

[0060] The above contents are further detailed descriptions of the present invention in combination with specific preferred implementation modes, and it cannot be determined that the specific embodiments of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a ceramic copper-clad laminate, characterized in that: The following steps are involved: S1, roughening the ceramic surface to form a substrate surface; S2, spraying a transition coating on the outside of the substrate surface using a high-speed arc spraying device, wherein the transition coating comprises an aluminum alloy; S3. Using high-speed arc spraying equipment to spray a copper coating on the outside of the transition coating, wherein the copper coating includes non-alloy copper.

2. The preparation method according to claim 1, characterized in that: The ceramic is selected from one of Si3N4, Al2O3 or AlN.

3. The preparation method according to claim 1, characterized in that: The transition coating consists of AlMg5.

4. The preparation method according to claim 3, characterized in that: In step S2, high-speed arc spraying is performed using ER5356 welding wire.

5. The preparation method according to claim 1, characterized in that: The thickness of the transition coating is 80-100 μm.

6. The preparation method according to claim 1, characterized in that: The copper coating has a thickness of 100-3000 μm.

7. The preparation method according to claim 1, characterized in that: In step S3, high-speed arc spraying is performed using ERCu welding wire.

8. The preparation method according to claim 1, characterized in that: The roughening process in step S1 is laser ablation roughening process.

9. The preparation method according to claim 1, characterized in that: The compressed gas source pressure used by the high-speed arc spraying equipment is not less than 0.6 MPa.

10. A ceramic copper-clad laminate, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Ceramic copper-clad plate material and preparation method thereof

    CN117835536A